2003
DOI: 10.1097/00005537-200302000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life Assessment in Nonmelanoma Cervicofacial Skin Cancer

Abstract: Sun-protective behaviors were positively associated with certain QOL subscale scores in the population in the study. General QOL instruments demonstrated minimal impact of nonmelanoma skin cancer on patients at initial diagnosis. However, general measures may not be sensitive to the impact of nonmelanoma skin cancer. The development of a more disease-specific instrument may be necessary to evaluate this disease process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
64
0
4

Year Published

2003
2003
2016
2016

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(72 citation statements)
references
References 21 publications
4
64
0
4
Order By: Relevance
“…Among its strengths is its applicability to many disease groups as well as the general population, so that it can be used to make comparisons between cancer patients and patients with other diseases as well as healthy populations. Since most studies of the HRQOL of cancer survivors lack either a non-cancer control group or broad normative data on non-cancer patients against which to compare the findings, this is a very important advantage in attempting to sort out the contribution of cancer to differences in HRQOL versus the effects of comorbidities and natural aging [3,6,15,31,41]. The SF-36 Health Survey has been used in several studies to assess HRQOL of cancer patients and has revealed different deficits in HRQOL, depending on the cancer entity, tumor stage, treatment-related side effects and late effects and progression of cancer, but also differences which are related to comorbidity, sex, age, partner status, socioeconomic status and other conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Among its strengths is its applicability to many disease groups as well as the general population, so that it can be used to make comparisons between cancer patients and patients with other diseases as well as healthy populations. Since most studies of the HRQOL of cancer survivors lack either a non-cancer control group or broad normative data on non-cancer patients against which to compare the findings, this is a very important advantage in attempting to sort out the contribution of cancer to differences in HRQOL versus the effects of comorbidities and natural aging [3,6,15,31,41]. The SF-36 Health Survey has been used in several studies to assess HRQOL of cancer patients and has revealed different deficits in HRQOL, depending on the cancer entity, tumor stage, treatment-related side effects and late effects and progression of cancer, but also differences which are related to comorbidity, sex, age, partner status, socioeconomic status and other conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Fewer comorbid conditions and increased use of sun-protective behaviors were associated with enhanced QOL. 17 It was revealed in the current study that basal cell carcinomas were found in 91.1% (n=51); squamous cell carcinomas were detected in 7.2% (n=4). Single location wise more lesions were located on the nose 22.1% (n=15) and forehead 17.6% (12).…”
Section: Discussionmentioning
confidence: 44%
“…Although the SCI was developed specifically for BCC and SCC patients and demonstrated impairment on the Emotional and the Appearance subscales in the validation study, in our study standardized scores (0 to 100) were all >75 [18]. This observation implicates that HRQoL impairment in our population (treated with imiquimod) is less than in patients who will have to be treated surgically, or that the SCI is only suitable for use in patients being treated surgically, since it was developed in a tertiary care Mohs surgery clinic [19]. …”
Section: Discussionmentioning
confidence: 72%
“…In the Skindex-17 this can be explained by the more generic aspect of the items in the questionnaire. The SCI however displayed good responsiveness before and after treatment in previous studies [19,20]. The only treatment assessed however was surgical treatment and the lesions were only located in the head and neck area.…”
Section: Discussionmentioning
confidence: 80%